Faktor-faktor yang Mempengaruhi Produksi Bawang Merah di Desa Tampo Kecamatan Anggeraja Kabupaten Enrekang - Mutalib, Abdul; -, Nurhapsa; Sriwahyuningsih, A. Erna (Lembaga Penelitian dan Pengabdian pada Masyarakat Universitas Bosowa, 2020)
The study was conducted using multiple linear regression analysis. The aim is to analyze how much the use of production factors are land area (X1), seeds (X2), labor (X3), fertilizer (X4) and insecticide (X5) on the production of shallots (Y). the coefficient of determination (R2) in this study is 0.967, meaning that the influence of factors of production on production can be explained by the independent variable (X) of 96.7%, the rest is explained by other factors outside this study. The value of F-count 140,811> F-table 2.60 at 95% confidence level so that H1 is accepted and H0 is rejected. This means that simultaneously there is a significant influence between the area of land, seeds, labor, fertilizer and insecticide on the production of shallots. Partially the area of land has a significant effect on production, while seeds, labor, fertilizer and insecticides have no significant effect on the production of shallots.